The effect of milling parameters on laminated carbon fibre reinforced plastic (CFRP) - Muhamad Khairussaleh, Nor Khairusshima; C.H., Che Hassan; A.G. , Jaharah; A.K.M., Nurul Amin (Universiti Teknologi Malaysia, 2012)
The demand is high in various applications for an inexpensive and feasible alternative to engineering material, namely, the carbon fibre reinforced plastic (CFRP) composite. CFRP is one of the main materials used as a substitute for glass and aramid in aerospace industries. However, many problems arise during machining. Abrasive wear, poor surface finish, burr, and de-lamination, among others, are the common difficulties encountered by the machinist. These problems occur because of the existence of carbon in the CFRP that affects the performance of the tool and the surface quality of the end product. A solid uncoated carbide end mill cutting tool and a CFRP panel with fibre orientation of 0/45° were used to investigate the machinability of CFRP composite during milling; a cutting speed of 16 m/min to 240 m/min with a feed rate of 0.0125 mm/tooth to 0.0125 mm/tooth were set. At higher cutting speed and feed rate, the performance of carbide cutting tool worsens, similar to the de-lamination factor. Tool life is longer at lower cutting speed and feed rate, but a better quality surface is achieved at higher cutting speed. The dimensional precision of CFRP is also better at higher cutting speed and lower feed rate.